IMPLEMENTATION OF THE SPECIAL FINANCIAL ASSISTANCE PROGRAMME FOR NEIGHBOURHOOD ASSOCIATIONS (BKKD RT) IN KUTAI KARTANEGARA REGENCY - Suka Madeyanto; Kus Indarto; Anwar Alaydrus (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyse and compare the implementation of the BKKD RT Programme in Loa Pari Village and Manunggal Jaya Village, Tenggarong Seberang Sub-district, based on standard indicators and policy objectives, resources, inter-organisational communication, characteristics of the implementing bodies, socio-economic and political conditions, as well as the attitudes of implementers, and the challenges and obstacles in the implementation of the policy. This study employs a qualitative approach with a comparative design. Data sources consist of primary data obtained through in-depth interviews with the district government, village government, village facilitators, and RT heads in both villages, and secondary data in the form of BKKD RT budget realisation documents for 2022–2025, accountability reports, and other supporting documents. Data collection techniques included interviews, documentation, and field observation. Data analysis employed an interactive model comprising data collection, data condensation, data presentation, and drawing conclusions. The research findings indicate that the implementation of the RT BKKD Programme in both villages has generally proceeded in accordance with policy standards and is supported by a clear bureaucratic structure. However, there are differences in implementation patterns. This study identified two typologies at the village level: the stable-procedural model in Loa Pari Village, characterised by consistent administrative compliance and structured support; and the adaptive-verificative model in Manunggal Jaya Village, characterised by dynamic administrative adjustments and a multi-layered verification process. The obstacles identified include delays in fund disbursement, changes in technical regulations, limitations in RT administrative capacity, and variations in community participation. These findings indicate that institutional capacity and the effectiveness of coordination are determining factors in the success of policy implementation.